KONSEP GENDER DALAM ISLAM - Meiliarni Rusli (Kafa`ah: Journal of Gender Studies, 2011)
Islam consider the concept of equality and justice. Islam teachings interpret of equality as something that is proportionally fair, put something in the its place, not as numerous or equally. The equality principles of gender in the Qur’an explained that women and men are equally as slaves, caliph on earth, recieved a preliminary agreement with God, Adam and Hawa are actively infolved in the cosmic drama and same potential achievement.Keywords : Gender and IslamCopyright © 2011 by Kafa`ah All right reservedDOI : 10.15548/jk.v1i2.75